Physical Education Teacher Creativity in Increasing Students' Interest in Learning At the Bengkulu Tengah Regency State Middle School - Saputra, Firman; Yarmani; Eko Nopiyanto, Yahya; Syafrial (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2024)
Abstrak Penelitian ini bertujuan untuk mengetahui tingkat kreativitas guru penjas dalam meningkatkan minat belajar siswa di SMP Negeri Kabupaten Bengkulu Tengah. Penelitian ini menggunakan metode kualitatif deskriptif. Informan dalam penelitian ini yaitu 8 orang guru Penjas dari delapan SMP Negeri Kabupaten Bengkulu Tengah. Teknik. Pengumpulan data dengan observasi, angket, wawancara dan dokumentasi. Berdasarkan hasil observasi diketahui guru penjas pada usia 20-29 tahun sebanyak 3 orang, guru berusia 30-39 tahun sebanyak 3 orang, guru berusia 40-49 sebanyak 2 orang. Diketahui juga semua guru penjas yang mengajar tingkat pendidikan terakhir adalah S1. Dengan 5 orang guru S1 jurusan penjas dan 3 orang lulusan S1 bukan jurusan penjas. Berdasarkan hasil angket dan wawancara dapat diketahui skor rata-rata angket dari delapan guru penjas menggunakan lima aspek kreatifitas adalah 74,5% yang termasuk dalam kategori baik. Maka dapat disimpulkan kreatifitas guru penjas dalam meningkatkan minat belajar siswa di SMP Negeri Kabupaten Bengkulu Tengah termasuk dalam kategori baik. Kata Kunci : Guru Penjas, Kreativitas, Minat Belajar Abstract This research aims to determine the level of creativity of physical education teachers in increasing students' interest in learning at State Middle Schools in Central Bengkulu Regency. This research uses descriptive qualitative methods. The informants in this research were 8 Physical Education teachers from eight State Middle Schools in Central Bengkulu Regency. Data collection techniques using observation, questionnaires, interviews and documentation. Based on the results of observations, it is known that there are 3 physical education teachers aged 20-29 years, 3 teachers aged 30-39 years, 2 teachers aged 40-49. It is also known that all physical education teachers who teach at the highest level of education are S1. With 5 undergraduate teachers majoring in physical education and 3 undergraduate graduates not majoring in physical education. Based on the results of questionnaires and interviews, it can be seen that the average questionnaire score from eight physical education teachers using the five aspects of creativity is 74.5% which is included in the good category and the interview results with an average score of 4 which is included in the good category. So it can be concluded that the creativity of physical education teachers in increasing students' interest in learning at State Middle Schools in Central Bengkulu Regency is included in the good category.  Keywords: Creativity, Interest in Learning, Physical Education Teacher.